EFEKTIVITAS MANAJEMEN KESISWAAN PADA SMP NEGERI 3 SAKTI KABUPATEN PIDIE - Adnan, Yusrizal, Niswanto (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2017)
ABSTRACT: The school principal has an important role to achieve the education goal in schools. To achieve the goals of education, it is closely related to the effectiveness of student management at the school. The purpose of this study was to determine the effectiveness of student management at State Junior High School (SMP Negeri) 3 Sakti of Pidie Regency. This research used the descriptive method with a qualitative approach. The data were collected through interviews, observation, and documentation. The subjects of this study were principal, teachers, and students of SMP Negeri 3 Sakti of Pidie Regency. The results showed that: (1) The planning process management of student at SMP Negeri 3 Sakti of Pidie Regency conducted by the principal together with student representatives at the beginning of the year has been effective, which includes program: Analysis of the needs of learners, the recruitment of students, selection of students, and orientation; (2) The process of implementation of management student at SMP Negeri 3 Sakti of Pidie Regency regarding the New Student Admission (PSB), implementation of coaching students, and teaching students not all effective, especially in coaching student discipline, coaching students who successfully graduate study and implementation of the teaching of students concerning the curricular, extra-curricular and co-curricular; and (3) The obstacles of student management at SMP Negeri 3 Sakti of Pidie Regency, there are two factors, they are internal factors and external factors of the executive management.Keywords: effectiveness, student management, learnersABSTRAK: Kepala sekolah mempunyai peranan yang penting untuk mencapai tujuan pendidikan di sekolah. Untuk mencapai tujuan pendidikan, erat hubungannya dengan efektivitas manajemen kesiswaan di sekolah. Tujuan penelitian ini adalah untuk mengetahui efektivitas manajemen kesiswaan pada SMP Negeri 3 Sakti Kabupaten Pidie. Penelitian ini menggunakan metode deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data dilakukan dengan: wawancara, observasi, dan dokumentasi. Subjek penelitian adalah: kepala sekolah, guru, dan siswa SMP Negeri 3 Sakti. Hasil penelitian menunjukan bahwa: (1) Proses perencanaan manajemen kesiswaan pada SMP Negeri 3 Sakti Kabupaten Pidie dilakukan oleh kepala sekolah bersama dengan wakil kesiswaan pada awal tahun telah efektif, yang meliputi program: Analisis kebutuhan peserta didik, rekrutmen peserta didik, seleksi peserta didik, dan orientasi; (2) Proses pelaksanaan manajemen kesiswaan pada SMP Negeri 3 Sakti Kabupaten Pidie yang menyangkut dengan Penerimaan Siswa Baru (PSB), Pelaksanaan pembinaan siswa, dan pengajaran siswa belum semuanya efektif terutama pada pembinaan disiplin siswa, pembinaan siswa yang telah tamat belajar dan pelaksanaan pengajaran siswa yang menyangkut dengan kurikuler, ekstra kurikuler, dan kokurikuler; dan (3) Hambatan-hambatan manajemen kesiswaan di SMP Negeri 3 Sakti ada dua faktor yaitu faktor internal dan faktor eksternal dari pelaksana manajemen.Kata kunci: efektivitas, manajemen kesiswaan, peserta didik